Numerical study of reinforced and prestressed concrete components under biaxial tensile stresses. (23rd February 2017) - Zobel, Robert; Curbach, Manfred
Abstract : The focus of this study was the numerical investigation of reinforced and prestressed concrete components under biaxial tensile stresses in ANSYS in order to display the state of stress in a containment wall. Solid elements were used for concrete, whereas beam elements were used for reinforcing steel. The description and representation of the nonlinear material behavior and the fundamental phenomena of the damage of the concrete was implemented by using an elastoplastic material model. As crack width, crack spacing, and the deformation behavior of components largely depend on the bond behavior, a node‐to‐node contact between reinforcement and concrete was used. Therefore, a specific bond model was implemented. In the longitudinal reinforcement direction, the bond model implemented defines the bond resistance as a function of the relative displacements between concrete and reinforcement.